A method for preparing porous graphene using vitrinite-rich bituminous coal

Through laser -induced technology, the porous graphene is prepared by mirror -rich cigarette coal, which solves the problem of complex preparation steps, high energy input, large pollution, and low yield in existing technologies. The development of coal -based carbon materials.

CN116002671BActive Publication Date: 2025-01-24CHINA UNIV OF MINING & TECH (BEIJING)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310013063.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-05
Publication Date
2025-01-24
Estimated Expiration
2043-01-05

AI Technical Summary

Technical Problem

The prior art has problems in preparing graphene with complicated preparation steps, high energy input, environmental pollution and low yields, and porous graphene materials with three-dimensional structures cannot be obtained.

Method used

Use laser -induced technology to use the mirror -rich and cigarette coal as raw materials. After crushing, grinding, pickling, water washing, and drying, it is loaded into graphite pupa. Essence

Benefits of technology

It achieves simple operation, economical and environmental protection, large output, large specific surface area of ​​porous graphene, and good graphitization effect. It is suitable for the rapid production of coal-based porous graphene-related materials and provides a new method for low-carbonization and cleaning of coal. ideas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116002671B_ABST
    Figure CN116002671B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of coal-based carbon materials in the clean and efficient utilization of coal, and specifically relates to a method for preparing porous graphene by using vitrinite-rich bituminous coal; using bituminous coal as a raw material, the method sequentially undergoes crushing, grinding, pickling, water washing and drying to obtain a powdered sample of low-ash fine particles, then the powdered sample is filled into a graphite crucible with a hollow circular aperture, and is processed by a tablet pressing tool to prepare a sample slice, and the entire slice sample is irradiated by laser in a defocused and vacuum environment to induce the coal-based porous graphene material; the prepared coal-based porous graphene has the characteristics of fewer layers and larger specific surface area, and the product has great potential application value in various optoelectronic devices, electrochemical devices, sensors and the like, which is of great significance for promoting the development of preparing high-value-added graphene and other carbon materials using coal as a carbon source, and also provides an attractive method and idea for the clean and low-carbon utilization of coal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of coal-based carbon materials in clean and efficient utilization of coal, and in particular to a method for preparing porous graphene by utilizing vitrinite-rich bituminous coal. Background Art

[0002] Graphene is a sp 2 A novel two-dimensional carbon material formed by a network of hybrid carbon atoms. Generally speaking, graphene is a single-layer structure, but in practical applications, a few-layer graphene (1-10 layers) can also show excellent performance. Therefore, in this field, structures with 10 or more layers are collectively referred to as graphene materials. Since graphene has the characteristics of ultra-high specific surface area, charge mobility, electrical conductivity, thermal conductivity, chemical stability and mechanical properties, it has important potential application value in Joule heat, electrochemical sensing, supercapacitors and high-performance electrocatalysis. Traditional preparation of graphene mostly adopts micromechanical exfoliation, epitaxial growth, chemical vapor deposition CVD, and graphene oxide reduction. However, there are many problems with the above methods, including complicated preparation steps, high energy input, large environmental pollution of chemical waste, and low yield. In addition, porous graphene materials with three-dimensional structures cannot be obtained. In order to solve the above problems, laser induction technology can be used to complete the preparation of three-dimensional porous graphene in one step. The preparation method has the advantages of simple operation, high processing efficiency, economy and environmental protection, and has attracted widespread attention from more and more people in recent years. The laser-induced porous graphene method mainly uses laser irradiation on the carbon precursor raw material to generate high temperature locally to quickly break the chemical bonds of the material, while new carbon-carbon bonds are reorganized to form sp 2 Hybridized carbon atom network graphene; In addition, a small amount of sp 3 Carbon atoms and other element atoms are quickly released in the form of gaseous substances. The generation of gas also promotes the formation of graphene's porous structure, giving it a larger specific surface area.

[0003] At present, the carbon precursor materials that can be used as laser-induced porous graphene are very limited. Most of them use commercial polymers such as polyimide PI, polyethylene PE, and carbon-rich raw materials such as wood rich in cellulose or lignin. The former is relatively expensive and easy to pollute the environment; while the latter often needs to be flame-retardant or carbonized before laser irradiation to prevent the raw materials from being rapidly decomposed and lost due to high temperature and oxidation, and to reduce carbon loss at high temperature. Therefore, exploring new graphene precursors remains an important topic. Coal is the cheapest and most abundant solid carbon material on the earth, with a carbon content generally higher than 50%, which provides a rich carbon source for the preparation of carbon materials. Therefore, upgrading coal as a carbon source to these high-value graphene carbon materials based on laser induction technology is a method with important application value, which is not only economically attractive, but also has significant benefits for the global environment. Summary of the invention

[0004] The present invention overcomes the deficiencies of the prior art and provides a method for preparing porous graphene using vitrinite-rich bituminous coal. The present invention uses a high-volatile, low-metamorphic bituminous coal as a raw material and uses laser-induced graphene technology to achieve the preparation of a variety of graphene materials including graphene, graphene mesoporous materials, etc. The method of the present invention has the advantages of simple operation, economy and environmental protection, relatively high output, large specific surface area of ​​the obtained porous graphene, good graphitization effect, and is suitable for the rapid production of coal-based porous graphene-related materials, finding a new way out for the utilization of coal.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing porous graphene using vitrinite-rich bituminous coal, taking bituminous coal as raw material, and sequentially undergoing crushing, grinding, pickling, water washing, and drying to obtain a low-ash fine-grained powder sample, and then filling the powder sample into a hollow circular aperture graphite crucible, and preparing it into a sample slice through a tabletting tool, and inducing the coal-based porous graphene material by laser irradiating the entire slice sample in a defocused and vacuum environment.

[0006] Furthermore, the bituminous coal is a high-volatile and low-metamorphic bituminous coal whose macroscopic coal rock type is bright coal.

[0007] Furthermore, the particle size of the bituminous coal after crushing and grinding is below 200 meshes.

[0008] Preferably, the pickling method is to sequentially undergo three-stage pickling treatments of dilute hydrochloric acid, hydrofluoric acid, and perchloric acid, with the concentrations of the three acids being 15%, 40%, and 72%, respectively; each acid treatment is kept in a constant temperature water bath at 60°C for 8 hours; after pickling, the sample is washed with ultrapure water until the filtrate is neutral when detected by pH test paper, and the drying temperature is 60°C for 24 hours.

[0009] Preferably, the container for filling the sample is a customized graphite crucible with a hollow circular aperture, with an outer diameter of 25 mm, an inner diameter of 7 mm, and a hole depth of 5 mm.

[0010] Preferably, the amount of each loading in the graphite crucible is only 50 mg, and is pressed into a 1 mm sheet.

[0011] Furthermore, the laser irradiation system used for laser induction consists of a laser, a cooling water circulation, a vacuum pump, a closed reaction chamber, a laser power supply, and a sample three-dimensional workbench, wherein the laser type is a commercial 1064 nm wavelength infrared CO2 continuous laser, and the laser rated power is 180 W.

[0012] Preferably, during laser induction, the spot diameter at the defocus position is 8 mm, and the laser power density is 3.58 W / mm 2 , laser irradiation time 120 s.

[0013] In addition, the present invention also provides a porous graphene material prepared by the above method for preparing porous graphene using vitrinite-rich bituminous coal.

[0014] The present invention also provides the use of the porous graphene material prepared by the above-mentioned method of preparing porous graphene using vitrinite-rich bituminous coal in assembling a three-electrode system electrochemical energy storage device.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention is to fill low-ash bituminous coal powder into a crucible, and crucibles of different pore sizes can be selected according to needs. Through laser irradiation and induction of bituminous coal, not only a large yield of porous graphene materials can be obtained, but also the graphitization effect is better. The whole process is simple to operate and formed in one time. There is no need to perform preliminary heating pretreatment (cross-linking process) on the sample, which is economical and environmentally friendly. The experimental results show that the porous graphene material obtained has a small pore size, a large specific surface area, and a good degree of graphitization. The obtained laser irradiation-induced coal-based product has important potential application value in sensors and capacitors. The present invention provides a new idea for the low carbonization and cleaning of coal, and broadens the development mode of coal-based carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Laser irradiation induced coal-based graphene system.

[0018] Figure 2 SEM images of coal samples before and after laser irradiation.

[0019] Figure 3a This is the low-temperature CO2 physical adsorption diagram after laser irradiation of coal sample.

[0020] Figure 3b This is the pore size distribution diagram of the coal sample after laser induction.

[0021] Figure 4a This is the Raman spectrum of the coal sample before and after laser irradiation.

[0022] Figure 4b XRD spectra of coal samples before and after laser irradiation.

[0023] Figure 5 XPS spectra of coal samples before and after laser irradiation.

[0024] Figure 6 HRTEM image after laser irradiation.

[0025] Figure 7a This is one of the cyclic voltammetry (CV) curves of laser-induced coal-based graphene electrode.

[0026] Figure 7b This is the second cyclic voltammetry (CV) curve of the laser-induced coal-based graphene electrode.

[0027] Figure 7c This is the constant current charge and discharge (GCD) curve of laser-induced coal-based graphene electrode.

[0028] Figure 7d This is the electrochemical impedance spectroscopy (ESI) curve of the laser-induced coal-based graphene electrode.

[0029] Figure 7e This is the cycling stability curve of laser-induced coal-based graphene electrode.

[0030] The following are marked in the figure:

[0031] 1-CO2 laser, 2-laser controller, 3-cooling water system, 4-vacuum pump, 5-reaction chamber, 6-focusing lens, 7-infrared thermometer, 8-three-dimensional working platform, 9-graphite crucible, 10-sample substrate. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments.

[0033] Example 1

[0034] A method for preparing porous graphene using vitrinite-rich bituminous coal comprises the following detailed steps:

[0035] 1) A piece of bituminous coal from the Datong Tashan mining area with a macroscopic coal type of bright coal, high volatile content and low metamorphic degree, was selected as the raw material, and crushed, ground, pickled, washed and dried in sequence: the coal was first crushed and ground into powder with a mortar and passed through a 200-mesh standard sieve, then 10 g of the powdered bituminous coal sample was weighed and placed in a polytetrafluoroethylene beaker, 300 ml of ultrapure water was poured into the sample to fully wet it, and then 50 ml of dilute hydrochloric acid (concentration 15%), 40 ml of hydrofluoric acid (concentration 40%) and 40 ml (72%) perchloric acid were placed in the beaker three times and mixed thoroughly, and after each mixing, the beaker was placed in a constant temperature water bath at 60 degrees Celsius for 8 hours, and stirred with a glass rod every 10 minutes during the insulation process, and after pickling, the acid solution in the coal was filtered out with a vacuum pump, and washed and filtered with ultrapure water until neutral, thereby obtaining a low-ash bituminous coal sample. This step is to reduce the influence of minerals on the product. The deashed sample was placed at 60 The samples were dried in a vacuum oven at ℃ for 24 hours and then sealed for storage.

[0036] 2) The low-ash bituminous coal sample was loaded into a graphite crucible and prepared into coal sample slices by a tabletting tool. The slices were irradiated for a short time under defocused conditions and vacuum environment: 50 mg of the dried deashed sample was weighed and loaded into a customized cylindrical graphite crucible with a hollow circular aperture of 7 mm. The crucible hole depth was 5 mm and the outer diameter was 25 mm. The sample was pressed with a tabletting tool to form a 1 mm thick slice. The sample in the crucible was then placed on an adjustable three-dimensional workbench. The X and Z axis positions of the three-dimensional workbench were adjusted to ensure that the laser spot was in the center of the base sample when the 1064 nm wavelength CO2 infrared laser irradiated the coal base.

[0037] 3) Using laser irradiation system to induce the preparation of porous graphene from bituminous coal Figure 1 , specifically:

[0038] 3.1) Build a laser irradiation induction system: Figure 1 As shown, the continuous wavelength laser emitted by the laser 1 is focused by the zinc selenide (ZnSe) focusing lens 6, with a focal length of 76.2 mm. The bituminous coal flake sample substrate 10 is placed on the three-dimensional workbench 8, and the Y axis of the three-dimensional workbench is controlled to make the sample in a defocused position. The spot diameter at the defocused position is 8 mm. The X and Z axes of the three-dimensional workbench 8 are adjusted to ensure that the surface of the bituminous coal sample substrate 10 is in the center of the laser spot, and the output laser power of the laser 2 is controlled at the same time; the laser wavelength of the laser in this system is 1064 nm, the output power is set to 180 W, the laser irradiation time is 120 s, and the laser power density during irradiation is calculated to be 3.58 W / mm 2The vacuum pump 4 is always running during the irradiation process to keep the reaction chamber 5 in a vacuum environment; the cooling water circulation system 3 is used to reduce the temperature of the laser tube, and the infrared thermometer 7 is used to test the temperature of the laser spot.

[0039] 3.2) The three-dimensional workbench 8 moves along the X-axis on the plane to determine the laser irradiation position to adapt to lasers with different laser power densities and laser induced processing at different defocus positions; by irradiating the surface of the coal sample substrate 10 with laser in a short period of time, porous graphene under different laser power densities can be induced to be prepared.

[0040] The obtained porous graphene product was subjected to characterization and performance verification experiments, including Raman, XRD, XPS, SEM, HRTEM, low-temperature CO2 adsorption and electrochemical performance testing of a three-electrode system (the electrolyte was 1 M H2SO4 aqueous solution).

[0041] Reference Figure 2 , Figure 2 The laser power density is 3.58 W / mm 2 , SEM images of bituminous coal substrate 10 before and after 1064 nm infrared continuous wavelength laser induction, Figure 2 middle ac This is the image of the product after laser induction. d This is an image of a coal sample. As the laser heats the sample, the temperature accumulates, causing some chemical bonds in the coal sample to decompose and form small molecular gaseous substances that are released. Under the action of gaseous fluid dynamics, a large number of microporous structures of different sizes are formed in the irradiated area, such as Figure 2 (ac).

[0042] Figure 3a The results of low-temperature CO2 physical adsorption after laser-induced 10-second exposure to a bituminous coal sample indicate that the presence of these micropores increases the specific surface area of ​​the material. The specific surface area of ​​the product induced in this example is 73.503 m 2 / g, the pore size is mainly distributed at 0.55 nm, such as Figure 3b As shown, the presence of these nanopores allows the electrolyte to penetrate more easily into the laser-induced product, thereby enhancing its electrochemical properties and making it an ideal electrode material.

[0043] Reference Figure 4a and 4b , Figure 4a and 4b 3.58 W / mm 2 Surface Raman and XRD patterns of the coal sample substrate 10 tested before and after continuous wavelength laser irradiation, where WJW is the coal sample and LIG-WJW is the laser induced product; Figure 4aAs shown in the figure, the test found that the product after laser induction showed the Raman spectrum of graphene. The coal samples before and after irradiation were at ~1350cm -1 Due to sp 2 The D peak produced by the breathing mode of hybrid carbon atoms is at ~1580 cm -1 By sp 2 The G peak is generated by the in-plane vibration of carbon atoms, while the G peak of the irradiated product is at ~2700 cm -1 There is an obvious 2D peak at the 2D point, which is a typical feature of two-dimensional graphite, and is composed of graphene layers randomly stacked along the c-axis. The sharp G and 2D peaks indicate that the bituminous coal has undergone a good graphitization reaction under laser irradiation, but there is still a relatively obvious D peak, indicating that there are still many structural defects in the irradiated coal sample, which causes more porous structures in the product. In addition, the strong 2D peak also shows that the induced product has a few-layer structural characteristics. Figure 4b As shown in the figure, after laser irradiation, the coal-based graphene product shows two obvious diffraction peaks at 2θ=25.8°(002) and 2θ=43.1°(100), respectively. According to the Bragg formula (1), the calculated graphene 002 crystal plane interlayer spacing is 0.345nm, which indicates that the laser-induced coal-based graphene has a high degree of graphitization.

[0044] Layer spacing d 002 : λ / 2sin θ 002 (1)

[0045] Reference Figure 5 , Figure 5 The coal sample base is 10 through 3.58 W / mm 2 XPS images before and after laser power density induction, where WJW is a coal sample and LIG-WJW is a laser-induced product. The XPS image shows the sp 2 The C=C bonds and π-π interactions are enhanced, which indicates that a larger sp 2 Mesh graphene sheets, sp 3 The CC bonds and oxygen- and nitrogen-containing chemical bonds are weakened, which also verifies that some weaker chemical bonds in the coal are broken and decomposed to form gaseous substances that are released. These results are consistent with the Raman and XRD results.

[0046] Reference Figure 6 , Figure 6 The coal sample base is 10 through 3.58 W / mm 2High-resolution transmission electron microscope images taken after laser power density induction. The image shows thin-layered graphene flakes with obvious bending and wrinkling structures. Through selection and analysis, the lattice fringe spacing of the laser product was measured to be 0.346 nm, close to the graphite layer spacing, which is consistent with the results shown by XRD. In addition, it was observed that the number of lattice fringe layers in other areas was less than 10, which ultimately proved to be graphene material.

[0047] Reference Figure 7a-7e , Figure 7a-7e The coal sample base is 10 through 3.58 W / mm 2 Electrochemical performance curve of coal-based graphene electrode prepared after laser power density induction. The CV curve is similar to a rectangle, but there are obvious reversible peaks (redox peaks) and tails in the curve, which indicates that the charge and discharge process exhibits dual electrochemical characteristics of dual capacitance and pseudocapacitance; the GCD curve presents a quasi-isosceles triangle, which indicates good coulomb efficiency, but in the GCD curve at low current density, there is an obvious pseudocapacitance inflection point, which is consistent with the CV curve results. According to formula (5), at a current density of 2 mA / cm 2 The lower electrode has a large specific capacitance, showing ideal charge and discharge performance; the ESI spectrum results show a low equivalent series resistance of 14.06 Ω, indicating that it has a faster ion migration rate and a lower internal resistance. At the same time, the slope of the low-frequency curve is large, indicating that the ion diffusion resistance is small (or a faster ion diffusion rate); from 2 mA / cm 2 It can be seen from the cyclic stability curve of current density that after 2000 cycles, the specific capacitance retention rate only decreased by 18.6%, showing good cyclic stability. These electrochemical performance results prove that laser-induced coal-based graphene has good electrochemical properties in 1M H2SO4 aqueous electrolyte, and it has great application prospects in the field of energy storage in the future.

Claims

1. A method for preparing porous graphene using vitrinite-rich bituminous coal, characterized in that: Bituminous coal is used as raw material, and a low-ash fine-grained powder sample is obtained through crushing, grinding, pickling, water washing, and drying. The powder sample is then loaded into a graphite crucible with a hollow circular aperture and processed into a sample slice by a tabletting tool. The coal-based porous graphene material is induced by laser irradiation of the entire slice sample under defocused and vacuum conditions. The bituminous coal is a high-volatile and low-metamorphic bituminous coal whose macroscopic coal rock type is bright coal; The container used for filling the sample is a custom-made graphite crucible with a hollow circular aperture, with an outer diameter of 25 mm, an inner diameter of 7 mm, and a hole depth of 5 mm; The graphite crucible is filled with only 50 mg each time and pressed into 1 mm thin sheets; During laser induction, the spot diameter at the defocus position is 8 mm and the laser power density is 3.58 W / mm 2 , laser irradiation time 120 s.

2. The method for preparing porous graphene using vitrinite-rich bituminous coal according to claim 1, characterized in that: The particle size of the bituminous coal after crushing and grinding is below 200 mesh.

3. The method for preparing porous graphene using vitrinite-rich bituminous coal according to claim 1, characterized in that: The pickling method is to use dilute hydrochloric acid, hydrofluoric acid, and perchloric acid in three levels, with the concentrations of the three acids being 15%, 40%, and 72%, respectively; each acid treatment is kept in a constant temperature water bath at 60°C for 8 hours; after pickling, the sample is washed with ultrapure water until the filtrate is neutral when detected by pH test paper, and the drying temperature is 60 degrees Celsius for 24 hours.

4. The method for preparing porous graphene using vitrinite-rich bituminous coal according to claim 1, characterized in that: The laser irradiation system used for laser induction consists of a laser, cooling water circulation, a vacuum pump, a closed reaction chamber, a laser power supply, and a sample three-dimensional workbench. The laser type is a commercial 1064 nm wavelength infrared CO2 continuous laser, and the laser rated power is 180 W.

5. A porous graphene material prepared according to the method for preparing porous graphene using vitrinite-rich bituminous coal according to any one of claims 1 to 4.

6. Use of a porous graphene material prepared by the method for preparing porous graphene using vitrinite-rich bituminous coal according to any one of claims 1 to 4 in assembling a three-electrode system electrochemical energy storage device.

Citation Information

Patent Citations

  • Methods of fabricating laser-induced graphene and compositions thereof

    US20190330064A1